Penyembuhan Luka Tanpa Bekas: Kemajuan dan Inovasi Terkini - Prakoeswa, Flora Ramona Sigit; Dzikri, Dykall Naf'an (PT Kalbe Farma Tbk., 2025)
Scarless wound healing, a hallmark of mid-gestation fetal skin, is characterized by minimal inflammation, balanced transforming growth factor-β isoforms, and a provisional extracellular matrix rich in type III collagen and hyaluronan. Decades of mechanistic studies have mapped how these features collectively enable rapid, regenerative closure without fibrosis. Contemporary adult-tissue strategies therefore focus on recapitulating the fetal milieu through targeted cytokine modulation, notably down-regulating TGF-β1/β2 while supplementing antifibrotic TGF-β3. Mesenchymal stem cells (MSCs) and their secretome have emerged as potent immunomodulators and angiogenic stimulants that steer wounds toward regeneration rather than scarring. Genetic engineering, biomaterial scaffolds, and extracellular-vesicle delivery platforms further enhance MSC persistence, homing, and paracrine potency. Parallel advances in bio-inspired hydrogels, microneedle arrays, and nanofiber dressings provide spatiotemporal release of growth factors, antimicrobial agents, and oxygen to orchestrate orderly repair. Such combinatorial nanotechnologies not only accelerate re-epithelialization but also limit hypertrophic collagen deposition, leading to flatter, more elastic neodermis.